A case of mood disorder with severe side effects of antidepressants in association with resistance to thyroid hormone beta with a THRB mutation - Hazuki Komahashi‐Sasaki; Norio Yasui‐Furukori; Ryo Maehara; Chie Hasegawa; Kazutaka Shimoda (Wiley, 2022)
Abstract Background Although resistance to thyroid hormone beta (RTHβ) is associated with attention‐deficit/hyperactivity disorder, there are few reports of other concomitant mood disorders in individuals with RTHβ. Case presentation A 67‐year‐old woman who had been previously diagnosed with RTHβ (Refetoff syndrome) came to our department as a depressed patient. She was hospitalized twice for depression and treated with antidepressants both times. Paroxetine (37.5 mg/day) treatment during the first hospitalization did not cause any side effects, but treatment with mirtazapine (15 mg/day) and venlafaxine (150 mg/day) during the second hospitalization caused clonus and disturbance of consciousness, and these adverse effects resulted in a prolonged period of hospitalization. Finally, the patient's symptoms were controlled with quetiapine (75 mg/day). Conclusion Poor tolerability to antidepressants was observed, which may be related to thyroid hormone intolerance. Low doses of quetiapine may contribute to improvements in depression.